Walking Gastrolinguistic Landscapes, with Metonymy as a Travel-guide : Šetnja gastrolingvističkim krajobrazom s metonimijom kao vodičem - Brdar, Mario (Array, 2021)
The present article is concerned with the role of metonymy in gastrolinguistic landscape, specifically with its role in creating a message for guests in the names of restaurants. Linguistic landscape is a relatively novel concept in contemporary linguistics, its methodology still in the flux, while its topics and approaches keep diversifying. The purpose of this article is to show that there is also a very important cognitive linguistic aspect to it. Specifically, the article points out the role of metonymy in creative examples of restaurant names that contain one or more elements from a language different from the rest of the restaurant name, focusing on the gastrolinguistic landscape of Central and Eastern Europe, primarily Croatia and Hungary. It is demonstrated that that in addition to some more general cultural models of language, speakers also have a multitude of specific folk models of particular languages, mostly based on stereotypes, which in turn are also metonymic. These activate a series of metonymic inferencing steps most of the time resulting in complex cumulative metonymies such that one is superimposed on the other, the target of one simultaneously functioning as the source for the next one, and so forth.